Ralentización del crecimiento y manufacturas en México - Isaac Leobardo Sánchez Juárez (Nóesis)
This article demonstrates the existence of a process of economic slowdown in the Mexican economy during the last twenty eight years, where the top result has been a shortfall in job creation. According to the Kaldorian's theory of growth, one factor explaining this situation is the lack of dynamism of the industrial-manufacturing sector. This is demonstrated through the use of an OLS model and Granger causality test. The results suggest that growth requires, among other things, a new industrial policy that encourages the development of manufacturing output under the current international context. This paper suggests some elements for the construction of such a policy.